In defense of Islam: American Muslim women write back - Abdul Manaf, Nor Faridah (IIUM Press and IIMU, 2009)
History of Islam in the United States of America: Islam is one of the fastest growing religions in the United States. There is no definite or exact number given afthe American Muslim population. One source says American Muslims make between 2.8 and 3.5 million of United States population although earlier claims were said to be between 5 million and 8 million (http://www.islamlOl.com/history/population2_usa.html. May 3, 2007). The common perception is that American Muslims are made of mainly immigrant pcpulation. This may be true of the 1960s in which the country witnessed an influx of Muslims, who were well-educated and politically astute, migrating to the United Stales. However, the history of African-American Muslims must not be overlooked for African Muslims sailed to America long before the slave trade came into existence.